CONDITION OF PHYSIOLOGY FISH TILAPIA (OREOCHROMIS NILOTICUS) ARREST IN THE PROCESS OF USING TOOLS TO CAPTURE ACTIVELY MONITORED ELECTROCARDIOGRAPH (ECG) - Armen, Wahyudi; ', Nofrizal; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in March 2013 with the object of Tilapia (Oreochromisniloticus). The research objects are counted by the number of heartbeats different currenttreatments. The purpose of this study was to determine the heart rate of tilapia(Oreochromis niloticus), a basic knowledge of predicting the rate of metabolism andrespiration and heart rate also determine the activity of tilapia at different swimmingspeeds, in the process of catching up with the use of active fishing gear. The higher theflow rate used in tilapia fishes the heart rate up, and seen in the relative heart rate rangingfrom (1.1 to 3.78), a portrait that fish require a lot of energy so that the fish is alsoincreasing the body's metabolisme.Keywords: Heartbeats, Tilapia (Oreochromis niloticus), Flow, Size Fish